2013
DOI: 10.18388/abp.2013_1963
|View full text |Cite
|
Sign up to set email alerts
|

A focus on homocysteine in autism.

Abstract: Homocysteine is an amino acid, which plays several important roles in human physiology. A wide range of disorders, including neuropsychiatric disorders and autism, are associated with increased homocysteine levels in biological fluids. Various B vitamins: B6 (pyridoxine), B12 (cobalamin), and B9 (folic acid) are required as co-factors by the enzymes involved in homocysteine metabolism. Therefore, monitoring of homocysteine levels in body fluids of autistic children can provide information on genetic and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 72 publications
2
36
0
2
Order By: Relevance
“…The first module also correlates with previous experimental findings in patients with ASD, that is, elevated homocysteine levels and oxidative tissue damage [Frye & James, ; Kałużna‐Czaplińska, Żurawicz, Michalska, & Rynkowski, ; Rose, Melnyk, Pavliv, et al, ; Rose, Melnyk, Trusty, et al, ], including hypomyelination due to excessive utilization of choline in remethylation processes [Steinfeld et al, ]. Thus, elevated levels of homocysteine might act as a false stimulatory molecule on n ‐Methyl‐ d ‐aspartic Acid glutamate receptors (MIM 138251), causing excitotoxicity, and subsequent apoptosis of nerve cells in the developing brain [Ramaekers, Sequeira, & Quadros, ].…”
Section: Discussionsupporting
confidence: 80%
“…The first module also correlates with previous experimental findings in patients with ASD, that is, elevated homocysteine levels and oxidative tissue damage [Frye & James, ; Kałużna‐Czaplińska, Żurawicz, Michalska, & Rynkowski, ; Rose, Melnyk, Pavliv, et al, ; Rose, Melnyk, Trusty, et al, ], including hypomyelination due to excessive utilization of choline in remethylation processes [Steinfeld et al, ]. Thus, elevated levels of homocysteine might act as a false stimulatory molecule on n ‐Methyl‐ d ‐aspartic Acid glutamate receptors (MIM 138251), causing excitotoxicity, and subsequent apoptosis of nerve cells in the developing brain [Ramaekers, Sequeira, & Quadros, ].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have revealed an association of hyper‐Hcy with several diseases, such as Alzheimer's disease, Parkinson's disease, and stroke . High levels of Hcy are also associated with neuropsychiatric disorders, including autism . Well‐controlled studies have demonstrated increased levels of Hcy in serum and urine in children with autism .…”
Section: Discussionmentioning
confidence: 99%
“…Hyper‐Hcy was shown to be linked with several diseases in the central nervous system, including Alzheimer's disease, Parkinson's disease, and stroke . Abnormally high levels of Hcy have also been observed in serum and urine samples of autistic children and are considered as a potential diagnostic marker for nutritional deficiency that is associated with improper functioning of autistic children . However, alteration of Hcy metabolism in ASD is not fully understood.…”
mentioning
confidence: 99%
“…1 Deficiency in the expression of enzymes, such as cystathionine b-synthase and cystathionine g-lyase or their cofactors, may lead to abnormal accumulation of Hcy, which is characteristic of inherited diseases such as homocystinuria and cardiovascular abnormalities. 2 GSH is the most abundant intracellular non-protein thiol. The ratio of free GSH to its oxidized state glutathione disulfide (normally 4100 : 1) is an indicator for the corresponding enzyme activity and the redox state of the cell.…”
Section: Introductionmentioning
confidence: 99%